2009
DOI: 10.2174/138955709788922610
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α Modulates Energy Metabolism in Cancer Cells by Inducing Over-Expression of Specific Glycolytic Isoforms

Abstract: To develop new and more efficient anti-cancer strategies it will be important to characterize the products of transcription factor activity essential for tumorigenesis. One such factor is hypoxia-inducible factor-1alpha (HIF-1alpha), a transcription factor induced by low oxygen conditions and found in high levels in malignant solid tumors, but not in normal tissues or slow-growing tumors. In fast-growing tumors, HIF-1alpha is involved in the activation of numerous cellular processes including resistance agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
295
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(309 citation statements)
references
References 130 publications
(196 reference statements)
11
295
0
3
Order By: Relevance
“…In fast-growing tumors, HIF-1· plays crucial roles in the activation of numerous cellular processes, including cell immortalization, cell growth and survival, invasion/metastasis, angiogenesis, resistance to chemotherapy, and overexpression of drug efflux membrane pumps (28,29). A recent report has shown that artemisinin induces DOX resistance by decreasing DOX accumulation and cytotoxicity in human colon cancer cells through the activation of HIF-1· and P-gp overexpression (30).…”
Section: Discussionmentioning
confidence: 99%
“…In fast-growing tumors, HIF-1· plays crucial roles in the activation of numerous cellular processes, including cell immortalization, cell growth and survival, invasion/metastasis, angiogenesis, resistance to chemotherapy, and overexpression of drug efflux membrane pumps (28,29). A recent report has shown that artemisinin induces DOX resistance by decreasing DOX accumulation and cytotoxicity in human colon cancer cells through the activation of HIF-1· and P-gp overexpression (30).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that HIF-3α also possesses transcriptional activity. All the hHIF-3α variants were demonstrated to be able to bind to HIF-β and overexpression of certain HIF-3α variants, together with HIF-β, induces the mRNA expression levels of several HIF-1 and HIF-2 target genes, including EPO (56,57), ANGPTL4 (58,59) and GLUT1 (60,61). However, the overexpression of HIF-3α variants reveals no significant stimulation of the expression of HRE-driven reporter genes (62), suggesting that the target genes induced by HIF-3α variants may contain specific response elements, which are not canonical HREs (31,62).…”
Section: Biological Functions Of Hif-3mentioning
confidence: 99%
“…These include glucose transporters (GLUT1, GLUT3), glycolytic enzymes (HKI, HKII, PFK-1, ALDO-A, ALDO-C, PGK1, ENO-a, PK-M2, PFKFB-3) and enzymes related to lactate production and lactate/proton extrusion (LDH-A, MCT4). 33,34 Hypoxia also induces the expression of the pyruvate dehydrogenase kinases (PDK1 and PDK3 isoforms), 26,35 which have different activities and specificities for the phosphorylation and inactivation of the three isoforms of pyruvate dehydrogenases (PDHA1, PDHA2 and PDHB), 36,37 which transform pyruvate into acetyl-CoA (Fig. 2).…”
Section: Tumor Cell Metabolism In Hypoxic and Normoxic Conditionsmentioning
confidence: 99%